Analisis sistem pengendalian intern pada dana pensiun bulanan di PT. Bank Mandiri Taspen KC Manado - Ermanti L; Claudia W. M Korompis (Yayasan Widyantara Nawasena Raharja, 2023)
The aim of this research is to find out directly the internal control system for monitoring monthly pension fund payments at PT. Bank Mandiri Taspen KC Manado.This research uses descriptive qualitative research. The data collection technique uses interviews, observation, and documentation. Data analysis was carried out based on the COSO control concept framework. The results of this research indicate that internal control of monthly pension funds at Bank Mandiri Taspen KC Manado has been effective. This is proven by the implementation of five components and 17 principles of internal control according to control theory.